STRUCTURAL ORGANIZATION AND VARIANT ANATOMY OF LOBULE I-III OF THE HUMAN CEREBELLAR VERMIS - Stepanenko, A.Yu.; Maryenko, N.I. (World of Medicine and Biology, 2012)
Variant anatomy of human cerebellar vermis lobules I, II and III is described. It is shown that the variability of the structure shown in their size, degree of differentiation of gray matter, the number and location of folia, their size and shape.